Adaptive Feed Plant Association Model For Improved Post-mining Land In Karangasem Regency - Suarna, W.; Candraasih K, N.N.; Duarsa, M.A.P. (Bumi Lestari Journal of Environment; Vol 14 No 1 (2014))
A study has been carried out to obtain the model legume association with superior grass plants that are adaptive to repair post-mining land on dry land. In the early stages, the research carried out on non-mining land to observe potential association models that predicted very suitable to recover the post-mining land. Experiment using a randomized block design with 12 combinations between grasses, legumes, and mycorrhizal and repeated three times. Grass used is Panicum maximum cvTrichoglumeand BrachiariaBrizanta, while legumes are used Centrocemapubescens and Clitoriaternatea. The results showed that based on analysis of growth and forage yield variables, almost all association models can be developed in dry land, and models the association between panikum, Brachiaria and centrocema can provide the highest results as much as 11.42 tons per ha of forage fresh or 1,37 tons of dry forage per ha .
Keywords: forage , association model plant , a dry land